Interaction in 3D virtual worlds: An integrated approach of emerging technologies in handball - Lopes, A.; Sequeira, P.; Morgado, L.; Madeira, A.; Ildefonso, J.; Pires, B.; Cardoso, M.; Dinis J. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Lifelong learning is a concept that is associated with changes in society as we know it. The new technologies of information and communication have contributed to the creation and development of various tools in the training, education and research in several areas. 3D virtual worlds are alternate realities in which people can interact with each other or elements present in it. In the field of education is recognized primarily by its potential ability to simulate complex situations, work collaboratively and also by "humanizing" the access and the transmission of knowledge asynchronously and synchronously. The purpose of this communication is to present: - the experiences acquired so far in handball, using the 3D virtual world of Second Life® as a training environment, and; - an integrated view of various emerging technological resources to assist coach, coaching and competition situations.